Analisis komunikasi matematis siswa pada materi relasi dan fungsi berdasarkan SOLO taxonomy ditinjau dari minat belajar siswa - Wahyuni, Astri; Angraini, Lilis Marina; Khoirunnisya, Melati; Elfina, Agus Linda (IKIP Siliwangi, 2025)
The objective of this research is to describe students’ mathematical communication in terms of student’s learning interests based on the SOLO Taxonomy level. The research method is a descriptive qualitative study conducted at SMPN 35 Pekanbaru grades VIII. The subject of this research is 8 students in grades VIII with high and medium learning interests. The research instruments used are a learning interest questionnaire and a mathematical communication test. The analysis consists of three stages: data condensation, displaying data, and drawing the conclusion. The research concludes there is no significant difference in students’ mathematical communication levels between medium and high learning interest students. Students with medium and high learning interests are on the multi-structural level. However, students with high learning interests put more effort into solving mathematics problems than students with medium learning interests. Therefore, efforts are needed, such as using the interactive learning model and media which increase the student’s learning interest to develop students’ mathematical communication ability.